Decentralized Participatory Governance under Digitalization: A Model Study - Nusrat Bano,; Umm-e-Rubab,; Dr. Muhammad Azhar,; Hassan Zafar,; Muhammad Rizwan Haleemi, (Al-Qanṭara, 2024)
Governance is a set of rules and regulations to run the country smoothly. Decentralization is the structural association of government-citizens relationship. Participation refers to involvement of citizens in affairs of government to promote inclusiveness. Digitalization is an emerging phenomenon to improve public services delivery, promote good governance and process of democratization. The research has been designed to examine whether or not reorientation of governance under ICT could promote more accurate participatory governance? The research aims to find out any association of participatory governance with informatization, good governance and decentralization. Additionally, E-governance and its mediating role with participatory governance have been analyzed. The study concluded that both the association of decentralization and E-governance could practice the participatory governance. Both qualitative and quantitative techniques are applied in this research.